THE ROLE OF LAW IN THE CONCEPT THEORY OF JUSTICE TO REBUILD NATION’S ECONOMY IMPACT OF COVID-19 OUTBREAK IN INDONESIA - Fikriya Afifiana Faizah (Universitas Slamet Riyadi, 2021)
The role of law in This study aims to obtain information about the role of law in efforts to develop the country's economy due to the Covid-19 outbreak in Indonesia which is reviewed based on Theory of Justice. The research method used is statute approach, the method of data collection through literature studies and qualitative normative data analysis techniques. The results of the study indicate that Indonesian government has taken extraordinary policies and steps in the context of saving the national economy and financial system stability through various relaxation policies relating to the implementation of the State Budget (APBN), especially by increasing spending on health, spending on social safety net, economic recovery, and strengthen the authority of various institutions in the financial sector. However, an oversight of the implementation of the policy is needed so that it is in accordance with the principles based on the General Principles of Good Governance to create justice for equality before the law.. Keywords: Role of Law, State Economy, Impact of COVID-19 outbreaks